Double diastereoselective [3,3]-sigmatropic aza-Claisen rearrangements. - Davies, S; Garner, A; Nicholson, R; Osborne, J; Savory, E; Smith, A (2003)
Asymmetric [3,3]-sigmatropic aza-Claisen rearrangement of the (Z)-N-allyl-N,O-silylketene aminal of (3S,4E,alphaR)-1-benzyloxy-3-(N-propionyl-N-alpha-methylbenzylamino)hex-4-ene furnishes (2S,3R,4E,alphaR)-N-alpha-methylbenzyl-2,3-dimethyl-7-benzyloxyhept-4-enamide in > 92% d.e.; rearrangement of the diastereomeric (3R,4E,alphaR)-(Z)-N,O-silylketene aminal proceeds with low diastereoselectivity.